Rice Cell Division Cycle 20s are required for faithful chromosome segregation and cytokinesis during meiosis. Issue 2 (1st December 2021) - Lin, Ya-Nan; Jiang, Chen-Kun; Cheng, Zhu-Kuan; Wang, Dong-Hui; Shen, Li-Ping; Xu, Cong; Xu, Zhi-Hong; Bai, Shu-Nong
Abstract: Chromosome segregation must be under strict regulation to maintain chromosome euploidy and stability. Cell Division Cycle 20 (CDC20) is an essential cell cycle regulator that promotes the metaphase-to-anaphase transition and functions in the spindle assembly checkpoint, a surveillance pathway that ensures the fidelity of chromosome segregation. Plant CDC20 genes are present in multiple copies, and whether CDC20s have the same functions in plants as in yeast and animals is unclear, given the potential for divergence or redundancy among the multiple copies. Here, we studied all three CDC20 genes in rice ( Oryza sativa ) and constructed two triple mutants by clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9-mediated genome editing to explore their roles in development. Knocking out all three CDC20 genes led to total sterility but did not affect vegetative development. Loss of the three CDC20 proteins did not alter mitotic division but severely disrupted meiosis as a result of asynchronous and unequal chromosome segregation, chromosome lagging, and premature separation of chromatids. Immunofluorescence of tubulin revealed malformed meiotic spindles in microsporocytes of the triple mutants. Furthermore, cytokinesis of meiosis I was absent or abnormal, and cytokinesis II was completely prevented in all mutant microsporocytes; thus, no tetrads or pollen formed in either cdc20 triple mutant. Finally, the subcellular structures and functions of the tapetum were disturbed by the lack of CDC20 proteins. These findings demonstrate that the three rice CDC20s play redundant roles but are indispensable for faithful meiotic chromosome segregation and cytokinesis, which are required for the production of fertile microspores. Abstract : Loss of all three rice Cell Division Cycle 20 genes caused male sterility, meiotic chromosome missegregation, aberrant spindle morphology, loss of meiotic cytokinesis, and disrupted tapetal function.